Empowering Nurses in Community Care to Prevent Domestic Violence: Strengthening Organizational and Personal Excellence (Journal of Universal Excellence, 2026)
Research Question (RQ): What is the role of community nurses in the prevention and management of domestic violence? How are community nurses dealing with different types of domestic violence in their patients? How can collaboration of community nurses and other members of the health team and external institutions be strengthened for better identifying and addressing domestic violence?Purpose: The aim of the study was to research the role of community nurses in the prevention and treatment of domestic violence.Method: In the study was used qualitative method. Data was collected with a purposeful sample of eight community nurses through semi structured individual interview. The first part of the questions included demographic features such as gender, age and years of working as community nurse. The second part of the questions was open-ended and focused on how community nurses use their knowledge and experience when dealing with domestic violence, what approaches they use and how they work with other members of the healthcare team and other related institutions. The data were analyzed using content analysis.Results: Research shows that community nurses play a key role in early identification of different types of domestic violence and in gaining the trust of victims. Accurate documentation and reporting of violence to the competent institutions is important for the protection of victims. The importance of additional training, better cooperation with competent institutions and protection of community nurses is also emphasized.Organization: This study highlights the need for additional education of community nurses for more affective identification of domestic violence. Also, organizations should develop common protocols and strengthened interinstitutional cooperation.Society: The study affects our society on social responsibility and improving the response to domestic violence. Raises awareness of the important role of community nurses in identifying and preventing domestic violence.Originality: It points to the need of additional education and training, and better cooperation with the responsible institutions, which would improve the approach to dealing with this issue.Limitations/Future Research: As far for the limitation of the study it is worth to mention that it included a small sample of participants. Through our literature search we noticed similar studies on this topic and protocols for dealing with domestic violence. Nevertheless, it seems that their availability and knowledge among nurses is still limited. This may contribute to problems in identifying and dealing with cases of domestic violence and with that on their effectiveness in their work. It would be beneficial to focus further research on exploring the level of awareness and knowledge of existing resources and protocols among community nurses and to consider how this knowledge can be better integrated into their practice.
Keywords: family environment; violence; preventive measures; community nurse; nursing